Learning Higher Mathematics with AI: A Phenomenological Study of Students’ Experiences - Dhakal, Bed Prasad (Interdisciplinary Research in Education, 2025)
This study is qualitative phenomenology research to explore the ‘students’ learning experience while using AI based learning resources in higher mathematics learning”. The scope of the study is particularly limited to a content “osculating plane”, which is a fundamental concept in Differential Geometry. This study employed interactive digital tools, specifically AI and JavaScript-based interactive simulations, to explore how it supports in enhancing student understanding in higher mathematics, as lived learning experience. The Technological Pedagogical Content Knowledge (TPACK) framework was used as a theoretical ground to analyze the data. This study is based among thirteen master's level students at Central Department of Education, Tribhuvan University, Nepal. The tools used in this study were classroom observation checklist and student interview guidelines. Being a phenomenological study, the data analysis focused on capturing and interpreting lived experiences and meanings, not on numerical comparison only. Based on the available data, interview transcripts and observation notes were coded, categorized into meaningful units, and synthesized into themes representing students lived experiences. Based on this analysis, this study found that integration of AI and JavaScript based interactive simulations in higher mathematics education learning resources, student enjoyed the learning with digital simulation and videos. These resources helped them to bridges the “conceptual learning gaps” and fosters “meaningful mathematical understandings”.